STRATEGI PEMASARAN PRODUK INDOMIE (PT INDOFOOD SUKSES MAKMUR ) DALAM PASAR INTERNASIONAL - Suhairi Suhairi; Cici Winda Atila; Diana Diana; Niken Rahmadiyah; Rio Ariangga Hutagalung; Wahyu Adriansyah Naibaho (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this study is to analyze how the company's strategy dominates the international market. PT Indofood Sukses Makmur Tbk is one of the companies that is able to enter the international market. The products of PT Indofood in this study sell their products in several countries. This type of research is descriptive qualitative research, namely scientific investigation that aims to understand a phenomenon in its natural social context through a process of in-depth communicative interaction between the researcher and the phenomenon being studied. From the results of this research, Indomie is the instant noodle brand of PT Indofood Sukses Makmur Tbk in Indonesia and is the largest instant noodle producer in the world with 16 factories that produce 15 billion packs of Indomie each year. Indomia is also exported to more than 60 countries around the world. The application of continuous innovation, namely the construction of factories abroad, product strategy, quality maintenance, pricing strategy, distribution strategy, promotion strategy, customer relationship (consumer relationship building strategy).